T105. CAN WE RECOMMEND COGNITIVE REMEDIATION THERAPY FOR SCHIZOPHRENIA?. (9th April 2019) - Rossell, Susan; Reser, Maree; Bryce, Shayden; Contreras, Natalia; Tan, Eric; Lee, Stuart
Abstract: Background: Cognitive impairment is a core feature of schizophrenia that contributes to functional disability. Pharmacological treatments have little to no effect on cognitive deficits. Cognitive remediation therapy (CRT) has emerged as a moderately effective treatment in ameliorating cognitive deficits. However, a number of limitations have been identified in the literature which have impacted the strength of recommendations for clinical translation. These include, but are not limited to: reported variability in response to CRT with some patients not realising any benefit; it is unknown to what extent there is functional generalisation; it is unknown what the role of intrinsic motivation on treatment engagement and response is; and finally, there has been limited previous research to examine the lived experience of participants as they engage with CRT programs. This presentation will review a compendium of recent studies conducted by this research group to address these issues. Methods: Study 1 completed a systematic review of the empirical research examining the possible mediators, moderators and predictors of cognitive outcome following CRT. Study 2 completed a single arm CRT intervention in a group of schizophrenia patients with the aim to investigate whether there were different responder groups and what factors might influence response. Study 3 was an assessor-blinded randomized controlled CRT versus computer game control study, which as well as examining impact on cognition and independent living skills also explored the role of intrinsic motivation on cognitive improvement. Study 4 and 5 qualitatively examined how schizophrenia patients experienced participation in CRT. Results: Study 1 identified premorbid IQ, baseline cognition, and learning potential as possible predictors of an individual's capacity to benefit from CRT. Study 2 demonstrated that fifty-five percent of this sample realised reliable change across at least one cognitive domain. Baseline attention/vigilance and verbal learning potential differentiated the CRT responders from non-responders. Study 3 demonstrated improvements in cognition but not independent living skills in the CRT group relative to the controls. It also reported that early perceptions of intervention value predicted session attendance, and positive changes in interest and value during the intervention increased the odds of reliable cognitive improvement. Throughout study 4 and 5 participants qualitatively reported positive experiences during CRT, including greater memory and community functioning, having learned new skills, and opportunities to overcome challenges which enhanced beliefs about capability. Discussion: The data presented addresses some of the important limitations identified in CRT research. However, there remains a critical need for large-scale investigations to further scrutinize critical mechanisms influential in CRT outcomes. In conjunction, there is a need for novel analytic techniques to aid a better formulation to influence treatment guidelines. Large-scale international consortia are needed to make substantial advances within this field.